Some biological and behavioral aspects of Amblyomma longirostre (Acari: Ixodidae) under laboratory and natural conditions - Luz, Hermes Ribeiro; Martins, Thiago Fernandes; Friciello Teixeira, Rodrigo Hidalgo [UNESP]; Terassini, Flavio Aparecido; Soares, Herbert Sousa; Soares, Joao Fabio; Horacio Faccini, Joao Luiz; Labruna, Marcelo B. (Systematic & Applied Acarology Soc London, Natural History Museum, 2018)
Amblyomma longirostre (Koch, 1844) has been reported as one of the most common ticks parasitizing wild animals in Brazil; however, information about its life cycle is inexistent, as well as information on its behavior in nature. In order to determine some aspects of the life cycle of A. longirostre in the laboratory, we performed infestations of larvae and nymphs on Serinus canaria (Common Canary - Passeriformes), Calomys callosus (Vesper mouse), Sphiggurus villosus (Brazilian porcupine), and Gallus gallus (chicks - no Passeriformes); this later host species only for larvae. While the overall recovery rates of engorged larvae and nymphs were low (at most 11.1%), the highest rates were for ticks that had fed on S. canaria (Passerifomes). This result is supported by field data, which indicate Passeriformes as preferable hosts for larvae and nymphs of A. longirostre. Interestingly, the suitability of the porcupine S. villosus as host for larvae and nymphs was statistically similar to S. canaria, although the recovery rates on the later host species were slightly higher. The Cricetidae mouse C. callosus displayed the lowest recovery rates (0-0.5%) of engorged ticks, indicating that mice might not be suitable hosts for A. longirostre under natural conditions. We also report three adult females of A. longirostre that were collected from two Bristle-spined porcupine Chaetomys subspinosus. Curiously, each of the three ticks was attached to the median third of a spine of the porcupines. The hypostome was surrounded by a cement-like structure at the spine external surface, but did not break through the external surface of the spine. Biological explanations for this behavior are discussed.
Keywords: Ixodidae; life cycle; birds; wild mammals; Brazil